2008
DOI: 10.1080/13546800701707371
|View full text |Cite
|
Sign up to set email alerts
|

Attentional capture in schizophrenia and schizotypy: Effect of attentional load

Abstract: The results suggest that attentional modulation is impaired in schizophrenia and in the schizophrenia spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 58 publications
5
18
2
1
Order By: Relevance
“…This suggests that the lesions have a direct effect on attentional capacity, reducing the amount of perceptual load necessary to induce early selection. Similar results have been observed in people with schizophrenia and schizotypal personality (Ducato, Thomas, Monestes, Despretz, & Boucart, 2008). There has been disagreement as to whether schizophrenia results in reduced or increased attentional capacity, with many studies producing different results using different paradigms.…”
Section: Individual Differences Under Loadsupporting
confidence: 69%
“…This suggests that the lesions have a direct effect on attentional capacity, reducing the amount of perceptual load necessary to induce early selection. Similar results have been observed in people with schizophrenia and schizotypal personality (Ducato, Thomas, Monestes, Despretz, & Boucart, 2008). There has been disagreement as to whether schizophrenia results in reduced or increased attentional capacity, with many studies producing different results using different paradigms.…”
Section: Individual Differences Under Loadsupporting
confidence: 69%
“…Importantly, studies with psychotic patients show deficits in the threat-superiorityeffect towards social stimuli (e.g., Leppänen et al, 2006;Namiki et al, 2007), but not towards non-social information (Pinkham et al, 2014). It is therefore possible that psychotic patients are more sensitive to the interference of irrelevant stimuli with emotional content at high perceptual load conditions, compared to low perceptual load, even with their limited processing resources (Ducato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, at low perceptual load, the remaining attentional resources are involuntarily directed to task-irrelevant stimuli, allowing its processing. Ducato et al (2008) have studied the perceptual load effects in schizophrenia using nonemotional stimuli and showed that, compared to controls, patients were more effective at inhibiting interference by task-irrelevant stimuli in the high and medium load, compared to the low load conditions. According to the authors, these effects were not the result of a heightened ability to selectively filter irrelevant information, but instead the result of limited available resources, i.e., a consequence of the higher demands of the task (Ducato et al, 2008;Granholm et al,1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that patients with schizophrenia are more sensitive to distraction than healthy controls. 23,35 In our study, it might be that a salient feature in the object (e.g., colour, contrast edges) automatically captured the patients' attention and that they found it difficult to disengage their attention from that feature. Moreover, studies using the antisaccade paradigm have demonstrated that patients show difficulty inhibiting a reflexive saccade.…”
Section: Discussionmentioning
confidence: 99%